Ixazomib as Postinduction Maintenance for Patients With Newly Diagnosed Multiple Myeloma Not Undergoing Autologous Stem Cell Transplantation: The Phase III TOURMALINE-MM4 Trial - Dimopoulos, Meletios A; Špička, Ivan; Quach, Hang; Oriol, Albert; Hájek, Roman; Garg, Mamta; Beksac, Meral; Bringhen, Sara; Katodritou, Eirini; Chng, Wee-Joo; Leleu, Xavier; Iida, Shinsuke; et al. (Journal of clinical oncology, 2020)
PURPOSE: Maintenance therapy prolongs progression-free survival (PFS) in patients with newly diagnosed multiple myeloma (NDMM) not undergoing autologous stem cell transplantation (ASCT) but has generally been limited to immunomodulatory agents. Other options that complement the induction regimen with favorable toxicity are needed. PATIENTS AND METHODS: The phase III, double-blind, placebo-controlled TOURMALINE-MM4 study randomly assigned (3:2) patients with NDMM not undergoing ASCT who achieved better than or equal to partial response after 6-12 months of standard induction therapy to receive the oral proteasome inhibitor (PI) ixazomib or placebo on days 1, 8, and 15 of 28-day cycles as maintenance for 24 months. The primary endpoint was PFS since time of randomization. RESULTS: Patients were randomly assigned to receive ixazomib (n = 425) or placebo (n = 281). TOURMALINE-MM4 met its primary endpoint with a 34.1% reduction in risk of progression or death with ixazomib versus placebo (median PFS since randomization, 17.4 v 9.4 months; hazard ratio [HR], 0.659; 95% CI, 0.542 to 0.801; P < .001; median follow-up, 21.1 months). Ixazomib significantly benefitted patients who achieved complete or very good partial response postinduction (median PFS, 25.6 v 12.9 months; HR, 0.586; P < .001). With ixazomib versus placebo, 36.6% versus 23.2% of patients had grade ≥ 3 treatment-emergent adverse events (TEAEs); 12.9% versus 8.0% discontinued treatment because of TEAEs. Common any-grade TEAEs included nausea (26.8% v 8.0%), vomiting (24.2% v 4.3%), and diarrhea (23.2% v 12.3%). There was no increase in new primary malignancies (5.2% v 6.2%); rates of on-study deaths were 2.6% versus 2.2%. CONCLUSION: Ixazomib maintenance prolongs PFS with no unexpected toxicity in patients with NDMM not undergoing ASCT. To our knowledge, this is the first PI demonstrated in a randomized clinical trial to have single-agent efficacy for maintenance and is the first oral PI option in this patient population.
Keywords: Proteasome Inhibitors; Male; Boron Compounds; Treatment Outcome; sloučeniny boru; lidé středního věku; protinádorové látky; inhibitory proteasomu; glycin; transplantace kmenových buněk; Humans; mnohočetný myelom; Middle Aged; senioři; Antineoplastic Agents; mužské pohlaví; Multiple Myeloma; Female; Aged; Glycine; doba přežití bez progrese choroby; ženské pohlaví; udržovací chemoterapie; Stem Cell Transplantation; Double-Blind Method; Progression-Free Survival; Maintenance Chemotherapy; lidé; Placebos; dvojitá slepá metoda; placebo; výsledek terapie